2011
DOI: 10.4236/ijcm.2011.23050
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Patients with Pectus Excavatum as an Indication for Therapy

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…However, based on our clinical experience and reported data, it has been observed that Nuss procedure outcomes following bar removal are not always satisfactory. This is a problem because the process is used to correct a deformity that inflicts psychological and social harm in patients [25]. Therefore, a great deal of progress must be made before perfect surgical results may be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on our clinical experience and reported data, it has been observed that Nuss procedure outcomes following bar removal are not always satisfactory. This is a problem because the process is used to correct a deformity that inflicts psychological and social harm in patients [25]. Therefore, a great deal of progress must be made before perfect surgical results may be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…3,7 The consequences of these emotions manifest in avoidance to participate in sports and other activities, which may impact their overall physical and social development. Patients will often present not with physical symptoms, but rather those arising from a psychological cause.…”
Section: ■ Effect On Body Imagementioning
confidence: 99%
“…Patients will often present not with physical symptoms, but rather those arising from a psychological cause. 7 A study by Habelt et al investigated the psychological distress felt by children with pectus excavatum and whether this could be a justifi ed indication for treatment of the disorder. 3,7 The consequences of these emotions manifest in avoidance to participate in sports and other activities, which may impact their overall physical and social development.…”
Section: ■ Effect On Body Imagementioning
confidence: 99%
See 1 more Smart Citation
“…В зарубежных исследованиях, посвященных психологическому состоянию подростков с указан-ным заболеванием [10][11][12], использовались преиму-щественно опросники, оценивающие те или иные признаки в баллах, которые обеспечили обширную базу знаний по данной проблеме. В настоящем ис-следовании мы стремились качественно оценить показатели, отражающие степень психологическо-го благополучия подростков с ВДГК, самооценку и тревожность.…”
unclassified